PERKEMBANGAN HAK PEREMPUAN DI BIDANG WARIS DALAM HUKUM ADAT BALI - Ni Nyoman Sukerti (Faculty of Law, Universitas Diponegoro, 2011)
Adat Jaw represent the law which live in the society, its for unwritten and still go into effect hitherto. Adat law studied by is the heritage of Balinese adat law. According to the heritage of Balinese adat law, daughter and widow of non as heir. Report of Research and justice decision mention that daughter as heir. Pursuant to the fact of woman rights in the heritage of Balinese adat law have experienced of the development. The development influenced by some factor of like paradigm change from some parent and some enforcer punish the Oudge), awareness of society citizen, individual evocation, education, economic of family, efficacy of family of to have a plan and legislation. The development, still have the character of limited namely only to its parent properties estae obtained do not by inherit.